EVALUASI PENGELOLAAN WAKAF PERSATUAN UMMAT ISLAM (PUI) DI KABUPATEN BOGOR DAN SOLUSINYA (PENDEKATAN METODE DELPHI) - Hendrawan, Herdi; Chaniago, Asdi; Sasongko, Aryo (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2025)
The potential for PUI waqf is enormous, however, the fact is that waqf management still encounters obstacles. This study identified problems that became obstacles in the management of PUI waqf, especially in Bogor Regency. The method used in this study is a quantitative method with the Delphi method of analysis. Based on the results of the Delphi analysis, the highest ranking obstacle is the lack of understanding and public awareness about waqf. As for the highest solution rating, there are three criteria, namely providing effective education and socialization to the public regarding good waqf, innovative waqf management from the PUI Waqf Asset Institution, and transparency and accountability of the PUI waqf asset institution. as well as transparency and accountability of PUI waqf asset institutions. The management solution offered by the expert is that each PUI institution looks for potential and productivity that can be developed, collaborates with other existing institutions, and consolidates PUI waqf assets. Increasing nazhir competence, developing waqf digitalization, participating in diversifying waqf products that have developed, strengthening the legal standing and certification of waqf land.